High Volumetric Energy Density of LiFePO4 Battery Based on Ultrasonic Vibration Combined with Thermal Drying Process. Issue 13 (30th September 2020) - Ren, Xin; Li, Zhenfei; Zheng, Yi; Tian, Weichao; Zhang, Kaicheng; Cao, Jingrui; Tian, Shiyu; Guo, Jianling; Wen, Lizhi; Liang, Guangchuan
Abstract : Increasing the compaction density of electrodes is an effective way to increase the volumetric energy density of the full battery. To avoid the problem of low compaction density, material breakage, and porosity decrease during the process of calendering, which greatly deteriorate the electrochemical performance of the battery, in this paper, for the first time, we use ultrasonic vibration-assisted densification technology combining with thermal drying technology to prepare the electrodes. Ultrasonic vibration reduces the friction among the powder particles during the drying process, so that the particles of active materials could aggregate more closely. And then, there are smaller displacements and sliding during the calendering process in ultrasonic vibration-assisted (UV–A) electrode than ordinary ones, which not only avoid the failure of the binder and the shedding of the carbon layer, also increase the number of connection points between material particles. The results show that the UV–A densification technology leads to improved volumetric energy density (increased by 5.3%, 6.6%, 7.6%, 11.6%, 13.4%, and 13.0% compared to the ordinary battery at 0.2C, 0.5C, 1C, 2C, 5C, and 10C, respectively), cycle performance and ion conductivity of full battery.